Jerzy Tomala: economist of growth and development - Małgorzata Madrak-Grochowska (Ekonomia i Prawo, 2019)
Motivation: The year 2018 was celebrated at the Faculty of Economic Sciences and Management of Nicolaus Copernicus University in Toruń, Poland as the 50th anniversary of the existence of the Faculty. To celebrate this jubilee, numerous conferences, debates, conventions and occasional meetings were organized. On the occasion of these events, people who contributed greatly to the development of the Faculty of Economic Sciences and Management in the area of science and didactics as well as in the organizational field were recalled and honoured. Undoubtedly, Professor Jerzy Tomala was one of them. Aim: The aim of this article is to present the biography of Professor Jerzy Tomala with special emphasis on his scientific accomplishments, international successes, as well as didactic and organizational achievements at the Faculty of Economic Sciences and Management of Nicolaus Copernicus University in Toruń, Poland. Results: During many years of his scientific work, Professor Jerzy Tomala became a scholar who was recognised both in Poland and internationally — first and foremost as an authority in the field of broadly understood macroeconomic problems of economic growth (with particular emphasis laid on the impact of investment, technological progress and efficiency of technical and economic relations on the long-term growth of national income) and in the area of economic policy of developed countries, mainly of the United States of America. His scientific interests also included the issue of full employment, the concept of a potential national product and educational policy. Professor Jerzy Tomala was invited to various study internships at renowned universities in the United States and to renowned scientific and teaching institutions in Western Europe. He also worked as a consultant of the World Bank, and his publications impacted some important decisions made by international organizations such as, for instance, OECD, the European Community, or the World Bank. For his achievements in the field of science, didactics and organizational work, Professor Jerzy Tomala received high state awards, prestigious awards of the Minister of Higher Education and the Rector of Nicolaus Copernicus University in Toruń, as well as numerous honours from his students and alumni.